Study of In-migration in Lucknow district, Uttar Pradesh - Alok Kumar Choubey; Choubey, Gayatri Rai (National Geographical Journal of India, 2022)
Internal migration is the movement of population within the administrative boundary of a country which includes both in-migration and out-migration. Flows and stocks of internal migration differ considerably due to differential characteristics of the moving population as well as conditions prevailing in the areas under migration. In-migration in Lucknow district has greatly increased in the last few decades due to high urbanisation, administrative convenience, abundant economic opportunities, improved residential amenities and the presence of higher-order services. In-migration is accounting for nearly 40 per cent of the total population of Lucknow district. The present paper aims to study the volume, growth, types and causes of internal in-migration in Lucknow district for the period 2001-11, taking migration types and rural-urban differentials into account. The paper also shows the spatial distribution of inter-state migrants in the Lucknow district. Secondary data is obtained from the Census of India’s Migration D-series table. Census only provides in-migration data at the district level. The paper uses the place of last residence data to study the demographic aspects of in-migrants. The states of India are taken as study units to show the spatial patterns of inter-state in-migrants. Percentage and decadal change of in-migrants are used as a statistical measure. It was found that in-migration in the district is primarily driven by urbanisation. Intradistrict migration is rapidly increasing and distance remains the determining factor in the distribution of inter-state migrants. The study also reects the variations of in-migrants in terms of migration types and rural-urban differentials thereby facilitating comparative analysis. It is believed that the present study will enhance the concept and signicance of internal in-migration in the district.